2008
DOI: 10.1007/s12185-008-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid as a possible cause of acute pancreatitis even in the absence of hypertriglyceridemia

Abstract: The standard therapy for patients affected by acute promyelocytic leukemia (APL) is the administration of all-trans-retinoic acid (ATRA). ATRA therapy is usually well-tolerated, but it also has the potential to induce toxicity. The most severe side effect of ATRA is retinoic acid syndrome; the next is acute pancreatitis, which is a rare but serious adverse event mostly due to hypertriglyceridemia. We herein report a patient who developed ATRA-induced acute pancreatitis without hypertriglyceridemia.A 17-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[10][11][12] Here, we present a typical case of a 55year-old woman with APL who developed WE during treatment for AP after therapy with ATO and ATRA. Some previous cases [4][5][6][7][8][9] have reported that WE is induced by AP and that AP was induced by treatment with ATO and ATRA in patients with APL. However, no reports have described a case of a patient with WE and APL after treatment with ATO and ATRA, or examined whether the administration of ATO and ATRA could induce WE in patients with AP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Here, we present a typical case of a 55year-old woman with APL who developed WE during treatment for AP after therapy with ATO and ATRA. Some previous cases [4][5][6][7][8][9] have reported that WE is induced by AP and that AP was induced by treatment with ATO and ATRA in patients with APL. However, no reports have described a case of a patient with WE and APL after treatment with ATO and ATRA, or examined whether the administration of ATO and ATRA could induce WE in patients with AP.…”
Section: Introductionmentioning
confidence: 99%
“…Some cases reported that the occurrence of AP was related to the application of arsenic, and some cases were associated with the administration of retinoic acid, which was secondary to hypertriglyceridemia or differentiation syndrome. [4][5][6][7][8][9] Wernicke encephalopathy (WE) is caused by thiamine deficiency and is strongly related to malnutrition, which may result from chronic alcohol abuse, gastrointestinal surgery, prolonged vomiting, or chemotherapy. WE, which is regarded as an acute and severe neuropsychiatric syndrome, is characterised by symptoms of confusion, ophthalmoplegia, and gait ataxia.…”
Section: Introductionmentioning
confidence: 99%
“…I read with great interest the article by Hoshino et al [1] titled, ''All trans-retinoic acid as a possible cause of acute pancreatitis even in the absence of hypertriglyceridemia,'' in which the authors describe a very peculiar and rare case of a drug-related acute pancreatitis (AP).…”
mentioning
confidence: 99%
“…Hoshino et al [1] report the second case in the literature of AP following all-trans-retinoic acid (ATRA) that presented without hypertriglyceridemia, which is one of the common side-effects of this drug. They suggested that in this case, ATRA-induced pancreatitis may have been due to the combination of increased pancreatic injury secondary to the upregulation of proinflammatory cytokines, such as IL-8, IL-1b, and TNF-a allied to a blockade in the process of pancreatic repair by pancreatic stellate cells.…”
mentioning
confidence: 99%